Nasal High-Flow for Weaning Preterm Newborns with Risk of Chronic Lung Disease from nCPAP - Gregoraci Fernández, Angela; Comuñas Gómez, Juan José; Rodriguez-Losada, Olalla; Flores España, Vanessa; Gros Turpin, Anna; Pérez Hoyos, Santiago; Castillo Salinas, Félix (American Journal of Perinatology, 2021)
Objective The aim of the study is to compare the duration of oxygen therapy by using two methods of weaning from nasal continuous positive airway pressure (nCPAP) in very preterm babies.Study Design Between April 2014 and December 2016, 90 preterm <32 weeks and birthweight >1,000 g who, after at least 7 days on nCPAP, were clinically stable on <6 cm H2O and FiO2 <30% were randomly assigned to weaning directly from nCPAP or with nasal high flow therapy (nHFT). In the nCPAP group, pressure was gradually reduced until the infant was stable on 4 cm H2O and then discontinued. In the nHFT group, flow rate was reduced until the infant was stable at 3.l pm and then discontinued.Results Eighty-four infants completed the study. There were no differences between the groups for the primary outcome, duration of oxygen therapy (median 33 [14–48] versus 28 [15–37] days; p = 0.17). The incidence of moderate-to-severe bronchopulmonary dysplasia was similar. Weaning time was shorter in the nCPAP group (p = 0.02), but the failure rate was slightly higher although non-significant. In the nHFT group, we observed better perception of patient comfort and a lower incidence of severe nasal injury.Conclusion Weaning by nHFT compared with weaning directly off nCPAP does not prolong duration of oxygen therapy. Rather, it is associated with better perceptions of infant comfort among parents and lower rates of severe nasal injury.Key Points
Keywords: continuous positive airway pressure; nasal high flow therapy; weaning; preterm infants; chronic pulmonary disease